(untitled) (Al-Academy, 2025)
The research problem lies in the notion that preserving, safeguarding, disseminating, and studying heritage while making this process an enjoyable experience for visitors are among the core functions expected of a museum. This study specifically investigates whether the museum, particularly the Museum of Umm Al-Qura University, fulfills these anticipated and desired roles. This study aims to identify the ideal global roles of museums, examine the current educational, scientific, artistic, and cultural functions of Umm Al-Qura University Museum, and determine the potential roles the museum could adopt considering global technological advancements. The research underscores the importance of activating the museum’s functions to contribute to strengthening cultural identity and development. The research employs a descriptive methodology to achieve its objectives and to answer the central research question. The findings indicate that integrating modern technologies in the display and documentation of heritage significantly enhances the museum’s effectiveness and its ability to attract visitors. The importance of this research lies in its examination of the status of the Museum of Umm Al-Qura University and its potential for development. This includes improving the efficiency of display methods by employing modern technology and integrating it into museum exhibitions. The research also highlights the importance of developing the skills of museum staff so that the museum may serve as an educational and cultural space with recreational value. The preservation, documentation, and aesthetic presentation of heritage demonstrating its richness through advanced and modern display techniques can significantly increase public engagement and reinforce the museum’s role in documentation and exhibition. The study recommends focusing on the museum’s promotional strategies, including the creation of a visual identity that reflects the museum’s character, the development of a website that introduces the museum and its collections, and the implementation of interactive programs that attract and engage the public and stimulate interest in physical visits. To conclude, the study emphasizes the importance of improving visitor experience and appeal by developing the museum’s activities and programs, enhancing its touristic value through improved display techniques, providing adequate facilities and services, supporting educational and cultural programming, offering guidance services, and focusing on the design and architectural style of the museum building to ensure it reflects a distinctive and aesthetically pleasing architectural identity